2022
DOI: 10.1038/s41598-022-12724-1
|View full text |Cite
|
Sign up to set email alerts
|

X-ray nanoimaging of a transversely embedded carbon fiber in epoxy matrix under static and cyclic loads

Abstract: The initial stage of fatigue failure has not been thoroughly clarified for carbon fiber reinforced plastics (CFRPs). Although the initiation of fatigue cracks has been regarded to be interfacial debonding between the carbon fiber and polymer matrix, their detection among numerous carbon fibers, whose diameter is only 7 µm, is extremely difficult. In this study, a single carbon fiber was transversely embedded in a dumbbell-shaped epoxy sample to focus on the interfacial debonding and was observed using synchrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…If the degree of fatigue progression can be evaluated in situ by applying nondestructive testing, it is possible to estimate the remaining service life. The fatigue progression rate is considered to be correlated with microdamage such as micro-voids, micro-cracks, and fiber/resin interface delamination that occur in CFRP [2,3,4]. The authors proposed a fatigue damage evaluation method using active thermography, which has been applied as a non-destructive inspection method for aircraft composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…If the degree of fatigue progression can be evaluated in situ by applying nondestructive testing, it is possible to estimate the remaining service life. The fatigue progression rate is considered to be correlated with microdamage such as micro-voids, micro-cracks, and fiber/resin interface delamination that occur in CFRP [2,3,4]. The authors proposed a fatigue damage evaluation method using active thermography, which has been applied as a non-destructive inspection method for aircraft composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…32 Takahashi et al observed localized debonding and voiding in a single-CF epoxy resin using synchrotron radiation X-ray computed tomography upon applying stress or cyclic stress to the sample. 36 As a different method to investigate the interface between (CF/matrix polymer), Raman spectroscopy and dynamic birefringence measurements have been performed to investigate stress transfer near the CF during the elongation process. 37−42 Finite elemental analyses of the stress field have also been performed, and various models have been reported to account for fiber rupture, plastic deformation, crack propagation, and shear lag.…”
Section: Introductionmentioning
confidence: 99%
“…Synchrotron radiation X-ray can be used to evaluate not only CFs but also the orientation of the polymer chains and craze formation during uniaxial elongation. Furthermore, when the microbeam X-ray is used for this measurement, information on the interface between (CF/matrix polymer) may be obtained by mapping. Schneider et al reported spatial distribution of failed interface and voids near the broken fiber edges in the epoxy matrix near the glass fibers in a stretched sample using microbeam small-angle X-ray scattering (SAXS) . Takahashi et al observed localized debonding and voiding in a single-CF epoxy resin using synchrotron radiation X-ray computed tomography upon applying stress or cyclic stress to the sample . As a different method to investigate the interface between (CF/matrix polymer), Raman spectroscopy and dynamic birefringence measurements have been performed to investigate stress transfer near the CF during the elongation process. Finite elemental analyses of the stress field have also been performed, and various models have been reported to account for fiber rupture, plastic deformation, crack propagation, and shear lag. …”
Section: Introductionmentioning
confidence: 99%